Continuity and change in political culture Israel and beyond - Aronoff, Yael, 1968-; Peleg, Ilan, 1944-; Sarsar, Saliba G., 1955-; Aronoff, Myron J. (Myron Joel), 1940- (Lexington Books, 2020)
"Leading scholars and practitioners of politics, political science, anthropology, Israel studies, and Middle East affairs examine aspects of continuity and change in political culture in tribute to Professor Myron J. Aronoff, whose work on political culture has built conceptual and methodological bridges between political science and anthropology"--